Slit sense organ distribution on the legs of two species of orb-weaving spider (Araneae: Araneidae). (March 2022) - Miller, Thomas E.; Taylor, Graham K.; Mortimer, Beth
Abstract: Biotic and abiotic mechanical stimuli are ubiquitous in the environment, and are a widely used source of sensory information in arthropods. Spiders sense mechanical stimuli using hundreds of slit sense organs (small isolated slits, large isolated slits, groups of slits and lyriform organs) distributed across their bodies and appendages. These slit sense organs are embedded in the exoskeleton and detect cuticular strain. Therefore, the spatial pattern of these sensors can give clues into how mechanical stimuli from different sources might be processed and filtered as they are transmitted through the body. Here, we map the distribution of slit sense organs on the legs in two species of orb-weaving spider, A. diadematus and T. edulis, in which slit sense organ distribution has not previously been investigated. We image the spiders' legs using scanning electron microscopy, and trace the position and orientation of slits on these images to describe the distribution and external morphology of the slit sense organs. We show that both species have a similar distribution of slit sense organs, with small isolated slits occurring in consistent lines parallel to the long axis of the legs, whilst large isolated slits, groups of slits and lyriform organs appear in fixed positions near the leg joints. Our findings support what has been described in the literature for several other species of spider, which indicates that slit organ arrangement is conserved across spiders in different evolutionary lineages and with disparate hunting strategies. The dispersed distribution of small isolated slits along the whole length of the leg may be used to detect large-scale strain of the leg segment as a result of muscle activity or internal changes in haemolymph pressure. Highlights: Slit sense organ map in Araneus diadematus and Trichonephila edulis . Small isolated slits distributed in lines parallel to long axis of leg. Lyriform organs, groups of slits, large isolated slits located at leg joints. Overall slit sense organ distribution important for mechanosensing.